2007
DOI: 10.1093/nar/gkm493
|View full text |Cite|
|
Sign up to set email alerts
|

Phospho-epitope binding by the BRCT domains of hPTIP controls multiple aspects of the cellular response to DNA damage

Abstract: Human (h)PTIP plays important but poorly understood roles in cellular responses to DNA damage. hPTIP interacts with 53BP1 tumour suppressor but only when 53BP1 is phosphorylated by ATM after DNA damage although the mechanism(s) and significance of the interaction of these two proteins are unclear. Here, we pinpoint a single ATM-phosphorylated residue in 53BP1—Ser25—that is required for binding of 53BP1 to hPTIP. Binding of phospho-Ser25 to hPTIP in vitro and in vivo requires two closely apposed pairs of BRCT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 31 publications
5
107
2
4
Order By: Relevance
“…This phosphorylation does not affect DNA repair (61), but it is necessary for 53BP1 binding to the BRCT domains of hPTIP (62,63), and its abrogation results in reduced CHK2 activation (63). This is consistent with the effect of VRK1 loss on CHK2 activation (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…This phosphorylation does not affect DNA repair (61), but it is necessary for 53BP1 binding to the BRCT domains of hPTIP (62,63), and its abrogation results in reduced CHK2 activation (63). This is consistent with the effect of VRK1 loss on CHK2 activation (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…First, in an interesting study carried out in mouse models (31), haploid inactivation of ASC-2 was found to accelerate polyoma middle-T antigen-induced mammary tumorigenesis. Second, PTIP, which has been proposed to play important roles in cellular responses to DNA damage (32,33), recently was identified as an additional component of ASCOM (9,10). In this regard, it is important to note that the tumor suppressor p53 plays a key role in countering the adverse effects of DNA damage (23), which otherwise can be lethal or lead to oncogenic transformation, and that DNA damage induces the transcriptional activity of p53 via damage sensors such as ATM (23).…”
Section: Targeted Inactivation Of Mll3 H3k4 Methyltransferase Activitmentioning
confidence: 99%
“…One includes the histone H3K4 methyltransferase ALR and its associated cofactors, the other contains DNA damage response proteins, including 53BP1 and SMC1 (30,31). Further experiments have revealed that DNA damage enhances the interaction between PTIP and 53BP1 (18,31).…”
mentioning
confidence: 99%